Numerical modeling of sensors based on long period gratings in photonic crystal fibres - Petrovic, Jovana S.; Dobb, Helen L.; Mezentsev, Vladimir K.; Kalli, Kyriacos; Webb, David J.; Bennion, Ian (My University, 2007)
A numerical model of the sensitivity of long period gratings fabricated by electric-arc in photonic crystal fibres to strain, temperature and refractive index is proposed and evaluated by comparison to the experimental results. It is shown to be superior to the commonly used semi-analytical method. The generalized modelling procedure is thoroughly explained in order to facilitate its application to a wide range of long period gratings in different types of fibres.